Biochemical effect of obesity on male infertility - Munasinghe, D.A.L. (Faculty of Indigenous Medicine, University of Colombo, 2023)
Obesity is considered a global health issue affecting more than a third of the population and it may lead to various complications such as diabetes mellitus (type 2), cardiovascular diseases, prostatic carcinoma, osteoarthritis, accelerated ageing, neurodegeneration infertility/subfertility in both male and female. Obesity of male can affect negatively on the quality of important seminal parameters such as sperm count, motility and morphology. This review study was launched to find out the biochemical mechanism of the effect of obesity on seminal parameters hence the male infertility. Based on the review result, it is proved that obesity has a negative effect on the quality of seminal parameters mainly on sperm count and motility. Due to the fact that these two parameters play an important role in male fertility, obesity has a negative impact on male fertility. Furthermore, the outcome of the review study could be considered as a platform for launching further researches on the topic and to consider the weight management more and more in the treatment regime of male infertility. Moreover, weight management may prevent certain other pathological conditions as well. This could be an additional advantage for the infertile/sub fertile patients.
Keywords: male obesity; biochemical mechanism; insulin; leptin; seminal parameters